ENGLISH MASTERY OF PNM STUDENTS ON ENGLISH PROFICIENCY TEST CRITERIA - Eda Maaliah (Universitas Katolik Widya Mandala Surabaya, 2023)
This research discussed the english mastery map of PNM students using EPT as a parameter to the study program and the possible steps that will be taken by the institution as a follow-up to the implementation of the English exam. The writer wants to know four things in this research, namely how is: (1) the average of English mastery of PNM students (2) the mapping of English mastery on each study program, (3) the Listening, Structure, and Reading studentsâ€™ mastery, and (4) the academic program possibility as a follow-up to student English exams. This research was conducted at Madiun State Polytechnic, even semester involving 3.172 students as a source of data that provided EPT score scores as research data. This research uses descriptive method. The research data were analyzed quantitatively using lowest, highest, and average score and percentage as statistical tools. The research result related to the map of students' English mastery in the final semester is shown with the average 460. Then, the average from the highest score is English Program, information technology, computer control, railway, electrical engineering, automotive, business administration, accounting, and logam (366). The third, the mastery English from the highest is reading (79,1%), Listening (66,2%), and Structure (59,2%). And the last, there are some possible academic programs, they are holding EPT, increasing EPT score, EPT preparation class, international program, and as a qualification to graduateÂ